Benzyl- Isothiocyanates signaling in stomatal function of guard cells of Arabidopsis plants under biotic stress - Sarwar, Jahan; Noor Naimah Syafiqah, Nokman (2017)
Stomatal opening provides access to inner leaf tissues for many plant pathogens, so narrowing stomatal apertures may be advantageous for plant defense. Benzyl-isothiocyanate (BITC) is generated from leaf epidermis cell walls of Arabidopsis plants during damages by pathogens or anyway. The role of BITC on guard cells of Arabidopsis was justified. BITC at 50 M or more induced stomatal closing which was partially inhibited by diphenylene iodonium (DPI), N G -nitro-L-Arg-methyl ester (L-NAME) and catalase. BITC-induced reactive oxygen species (ROS) in guard cells were significantly inhibited by DPI and 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1- oxyl-3-oxide (cPTIO). BITC-induced ROS production was impaired in guard cells of atrbohD/F, respiratory burst oxidase homologues. BITC depleted glutathione (GSH) levels of guard cells to increase sensitivity of BITC to stomatal closure which was returned by the application of GSH. These results support that ROS and NO production and redox regulation in signaling of BITC to stomatal aperture to control insect attached.